It Is Not Too Late : Preparing for Asia's Next Big Earthquake - World Bank (Washington, DC, 2017)
Strong earthquakes strike frequently countries in East Asia and the Pacific, causing building collapses and extensive damage to infrastructure and, when centered near populated areas, heavy life losses. Urban areas, with their increasing concentrations of population and infrastructure, are particularly at risk from catastrophic losses with far-reaching economic repercussions and human loss. The next earthquake and other large earthquakes in the East Asia region in the near future are inevitable. This paper aims at delivering the best science, risk analysis, and engineering available to help policy makers and particularly those directly responsible for mitigation, preparedness, response and recovery to anticipate and prepare for earthquakes and build safer, more resilient societies. In particular, this paper emphasizes the strengthening of existing schools, hospitals and specific infrastructure that should result in the largest possible life loss reduction and the largest possible financial loss reduction in the public sector. The objective of this paper is to help to reduce earthquake risk through promoting safer construction, disseminating good practice for new and existing infrastructure, increasing the level of preparedness, and, particularly, promoting a decrease in existing risk and saving lives through strengthening of existing important public infrastructure.